An assessment on impacts of online education on training quality and satisfaction of tourism undergraduate students in a private university and managerial implications for educators - Trong, Nhan Pham Nguyen; Phi, Nguyen Tran Ngoc; Nguyen, Le Truong; Lan, Nguyen Mai; Thuy, Phuong Nguyen Thi (International research journal of management, IT and social sciences, 2021)
The COVID-19 pandemic has disrupted the learning activities of learners in a myriad of ways. Being severely affected by the fourth wave of infection recently, many universities in the South of Vietnam have also switched their learning method into online learning. This study was conducted to explore the effects of online learning on learning quality by utilizing a survey sample of undergraduate students in the field of tourism. Through quantitative data analysis, the research results show that the majority of respondents have an above-neutral level of satisfaction (above 3) when participating in answering questions about factors affecting online learning such as the quality of online learning, e-learning activities, criteria for assessing learning results, education and training issues, influencing factors and impacts of virtual tourism on tourism students. The research results might give managerial implications to universities adopting online learning about policies and measures to improve the school’s educational quality during the pandemic.